Oral health comprehension in parents of Saudi cerebral palsy children - Amjad H. Wyne; Nouf S. Al-Hammad; Christian H. Splieth (Elsevier, 2017)
Objective: To determine oral health comprehension among parents of cerebral palsy (CP) children. Methods: A self-administered questionnaire was utilized to obtain the required information. The study was conducted in two main centers for disabled children in Riyadh, Saudi Arabia. Results: Parents of all 157 CP children registered in the two centers completed the questionnaire. Mothers mostly (86.6%) completed the questionnaire. Majority (98.7%) of the parents knew the importance of dental health for general health. More than two-third (70%) of the parents thought that teeth should be brushed thrice daily or after each meal. About three in every ten (29.9%) parents were not aware of the beneficial effect of fluoride in preventing dental caries; and very few (9.6%) were aware of water as a source of fluoride. Almost all (98.7%) the parents knew that sugary foods caused dental caries. Three-fourth (75.8%) of the parents were not aware of the possible harmful effects of bottled juices on teeth. There were no significant (p > 0.05) associations between the parental age/gender with any of the dependent variables. Conclusion: Parents of CP children generally showed satisfactory oral health comprehension. However, they need further oral health education in several areas. Keywords: Oral health comprehension, Parents, Cerebral palsy, Children